WOW! resumes administrative careers : how to put together a winning resume - Lefkowitz, Rachel (McGraw-Hill, 1997)
Designed for secretaries and other office workers, this guide shows you how to use strategies to sell your special skills, talents, and achievements in a polished, powerful resume that dazzles employers. It helps to learn how to beat the competition with a targeted resume that zero's in on a prospective employer's exact needs.